Oracle database 12c SQL - Price, Jason (McGraw-Hill Education, 2014)
"This Oracle Press guide shows you how to retrieve and modify database information, use SQL Plus and SQL Developer, work with database objects, write PL/SQL programs, and much more. In-depth coverage of the latest SQL features and tools, performance optimization techniques, advanced queries, Java support, and XML is included. Carefully revised to cover SQL Plus, SQL Developer, and more "--